Siemes digital transformation case study towards organizational scale and success in electrical engineering industry - Buriak, Mykhailo; Lysenko, Sergii; Shevchenko, Roman (Національний університет "Запорізька політехніка", 2024)
This study investigates a range of scaling strategies for electrical engineering firms, with a focus on various crucial aspects such as internal innovation, strategic regional expansion, geographical proximity, and collaborative partnerships. Internal innovation is highlighted as a key driver of growth, as it allows firms to develop new technologies and processes that can differentiate them from competitors. Strategic regional expansion is discussed as a means to tap into new markets and leverage local opportunities, while geographical proximity is examined for its impact on operational efficiency and customer relationships. Collaborative partnerships are also emphasized for their role in enhancing capabilities and driving mutual benefits. The case study of Siemens AG serves as a prominent example, showcasing how digital technologies like the Internet of Things (IoT), artificial intelligence (AI), and cloud computing have significantly transformed their approach to scaling. Siemens AG's experience underscores how these technologies can support internal innovation, streamline regional expansion efforts, overcome geographical barriers, and foster effective collaborations. The article proposes a detailed framework in which digital transformation is central to driving these strategies. It argues that digital technologies are not just enablers but essential components that fuel innovation across various domains. Additionally, digital transformation is posited as a critical factor in facilitating smoother and more effective expansion into new regions, bridging geographical gaps that can otherwise impede growth, and enhancing collaborative efforts both within and outside the organization. By integrating these elements, businesses can achieve sustainable growth and maintain a competitive edge in an ever-evolving and challenging market landscape.is considered near the evaluation of efficiency of management an enterprise. Evaluation technology is realized on the basis of comparison of financial indexes, in particular to the analysis of indexes of profitability and analysis of business activity.

В проведеному науковому дослідженні розглядаються стратегії масштабування провідних міжнародних електротехнічних компаній, підкреслюється важливість запровадження внутрішніх інновацій, стратегічної регіональної експансії, географічної близькості та спільних партнерств. На прикладі компанії Siemens AG проілюстровано трансформаційний потенціал цифрових технологій, зокрема Інтернету речей, штучного інтелекту та хмарних обчислень, у реалізації цих стратегій в електротехнічній галузі як одній з найбільш перспективних з значним потенціалом для розвитку та зростання. На основі проведених аналітичних досліджень, зокрема різнорівневих опитувань менеджменту, керівників та співробітників електротехнічних компаній, виявлено основоположні фактори та компоненти які сприяють ефективному масштабуванню та цифровій трансформації компаній. У статті пропонується комплексна концепція яка базується на симбіозі Big Data Analytics, інтеграції систем управління взаємовідносинами з клієнтами (CRM) із знанням місцевого ринку та хмарними обчислення і оптимізацією ланцюга постачань, згідно з якою цифрова трансформація не лише стимулює розробку та впровадження інновацій, але й значно полегшує розширення, долає географічні розриви та посилює співпрацю, що, зрештою, сприяє сталому зростанню бізнесу в умовах дедалі динамічнішого та конкурентнішого ландшафту. Автори вважають, що дослідження довгострокової стійкості та стабільності цифрових систем, ефективності blockchain в промислових додатках, використання даних клієнтів і конфіденційності, а також впливу цифрових двійників на життєвий цикл продукту дадуть додаткову цінну інформацію для розуміння побудови ефективних стратегій організаційного масштабування. Отримані результати окреслюють вектор подальших наукових досліджень пов’язаних з вивченням кількісного впливу цифрової трансформації на бізнес та стратегію міжнародних корпорацій, оцінку адаптації працівників до цифрових змін, ефективність алгоритмів штучного інтелекту та внесок цифровізації в досягнення цілей сталого розвитку.
Keywords: change management; digital transformation; AI in management; IoT in management; organizational scale; innovation management; цифрова трансформація; організаційне масштабування; управління змінами; штучний інтелект в менеджменті; інтернет речей в менеджменті; управління інноваціями